THE IMPORTANCE OF PHYSICAL CULTURE IN MODERN UNIVERSITY EDUCATION - Ashurmatov A. T. (American Journals, 2023)
The article contains comments on the development of physical culture and sports, students' skills of high physical activity are formed for many years. Physical education also helps to develop moral, strong-willed qualities, providing physical preparation of the younger generation for life and educating the need for health as a vital value.
Keywords: Physical culture and sports, universities, students, physical development, physical education of students.